2016
DOI: 10.1186/s12888-016-0810-0
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression in Nepal: prevalence, comorbidity and associations

Abstract: BackgroundAnxiety and depression are two important contributors to the global burden of disease. In many developing countries, including Nepal, their prevalences are yet to be assessed.MethodsA nationwide cross-sectional study was conducted among a representative sample of Nepalese adults aged 18–65 years (N = 2100), selected by multistage random cluster sampling and interviewed at home during unannounced visits. The validated questionnaires included the Hospital Anxiety and Depression Scale (HADS), to detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
113
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(127 citation statements)
references
References 45 publications
9
113
5
Order By: Relevance
“…1) (Almeida-Filho et al, 2004, Arias-de la Torre et al, 2018, Asokan et al, 2018, Bartwal et al, 2017, Bekaroglu et al, 1991, Bergdahl et al, 2007, Bielecki et al, 2015, Blazer and Williams, 1980, Cakici et al, 2017, Cardona et al, 2015, Carpiniello et al, 1989, Cho et al, 1998, Clayton et al, 1972, de Oliveira et al, 2012, Deyessa et al, 2008, El-Sherbini et al, 2009, Golden et al, 2009, Hailemariam et al, 2012, Hallstrom and Persson, 1984, Jacobs et al, 1989, Jones-Webb and Snowden 1993, Kennedy et al, 1989, Luppa et al, 2012, Madianos et al, 2012, Mossie et al, 2016, Nahcivan and Demirezen, 2005, O'connor, 2010, Ohayon et al, 1999, Onrust et al, 2007, Pahkala et al, 1995, PS et al, 2017, Risal et al, 2016, Sapranaviciute-Zabazlajeva et al, 2014, Sinha et al, 2013, Skapinakis et al, 2013, Somhlaba and Wait, 2008, Stephenson-Cino et al, 1992, St John and Montgomery, 2009, Vezina et al, 1998, Ward et al, 2007, Yopp et al, 2015, Williams et al, 1992. All 42 ...…”
Section: Identification and Study Characteristicsmentioning
confidence: 99%
“…1) (Almeida-Filho et al, 2004, Arias-de la Torre et al, 2018, Asokan et al, 2018, Bartwal et al, 2017, Bekaroglu et al, 1991, Bergdahl et al, 2007, Bielecki et al, 2015, Blazer and Williams, 1980, Cakici et al, 2017, Cardona et al, 2015, Carpiniello et al, 1989, Cho et al, 1998, Clayton et al, 1972, de Oliveira et al, 2012, Deyessa et al, 2008, El-Sherbini et al, 2009, Golden et al, 2009, Hailemariam et al, 2012, Hallstrom and Persson, 1984, Jacobs et al, 1989, Jones-Webb and Snowden 1993, Kennedy et al, 1989, Luppa et al, 2012, Madianos et al, 2012, Mossie et al, 2016, Nahcivan and Demirezen, 2005, O'connor, 2010, Ohayon et al, 1999, Onrust et al, 2007, Pahkala et al, 1995, PS et al, 2017, Risal et al, 2016, Sapranaviciute-Zabazlajeva et al, 2014, Sinha et al, 2013, Skapinakis et al, 2013, Somhlaba and Wait, 2008, Stephenson-Cino et al, 1992, St John and Montgomery, 2009, Vezina et al, 1998, Ward et al, 2007, Yopp et al, 2015, Williams et al, 1992. All 42 ...…”
Section: Identification and Study Characteristicsmentioning
confidence: 99%
“…Urban experience contributes to tension-anxiety of citizens in nearly all ages from 10 to 60 years old (Dekker et al 2008, McKenzie et al 2013, Bruzzese & Klein 2016) through shaping the socioeconomic pressure, physical environment and social interactions (Galea 2011). Results from the Global Burden of Disease Study 2013 revealed that mental and substance disorders collectively accounted for 21.2% all-year life lost to disability (YLD) wherein anxiety was ranked ninth highest specific cause of YLD in both developed and developing countries (Risal et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the past studies, another cut-off point [4/5] in Thailand [40], and 17.2% in Vietnam [33]. It is noteworthy that depression among adults years) in a recently conducted nationwide study population in Nepal was also found to be higher than the global mean [41].…”
Section: Discussionmentioning
confidence: 99%
“…Health care practices are largely related to the social norms and values among the community members [11]. In countries like Nepal, there is still a widespread belief that disclosure of mental illness is an embarrassment and may lead to discrimination [41].The stigma associated with mental illness may contribute towards underreporting of mental as opposed to physical symptoms [44]. Using the same cut-off (5/6) of GDS-15, an almost similar prevalence of geriatric depression (47.0%) was reported from India [28], a country with more or less similar sociocultural attributes to Nepal.…”
Section: Discussionmentioning
confidence: 99%